2000
DOI: 10.1063/1.482044
|View full text |Cite
|
Sign up to set email alerts
|

Resonant ion-dip infrared spectroscopy of benzene–(water)9: Expanding the cube

Abstract: Resonant ion-dip infrared spectroscopy of the S 4 and D 2d water octamers in benzene-(water ) 8 and benzene 2 -( water ) 8The techniques of resonant two-photon ionization ͑R2PI͒, UV-UV hole-burning, and resonant ion-dip infrared ͑RIDIR͒ spectroscopy have been employed along with density functional theory ͑DFT͒ calculations to characterize the hydrogen-bonding topologies of three isomers of benzene-͑water͒ 9 . Isomers I and II, with R2PI transitions shifted, respectively, by ϩ77 and ϩ63 cm Ϫ1 from the benzene m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 46 publications
5
64
0
1
Order By: Relevance
“…Solid water clusters 383 the double resonance ion-dip infrared experiments on water clusters connected to benzene [38,108,109], and to phenol [110,111]. In particular, the stable symmetric cube structures of the octamer were reported for the (H 2 O) 8 -benzene cluster [112], and for water clusters with the phenol chromophore [113].…”
Section: General Characteristics Of Cluster Oh Stretch Spectramentioning
confidence: 98%
“…Solid water clusters 383 the double resonance ion-dip infrared experiments on water clusters connected to benzene [38,108,109], and to phenol [110,111]. In particular, the stable symmetric cube structures of the octamer were reported for the (H 2 O) 8 -benzene cluster [112], and for water clusters with the phenol chromophore [113].…”
Section: General Characteristics Of Cluster Oh Stretch Spectramentioning
confidence: 98%
“…For gas-phase organic molecules, e.g., uv-hole-burning spectroscopy coupled with R2PI spectroscopy has been used to differentiate the absorption spectra of different isomers [15,16]. Another promising route is to separate a gas-phase isomeric ion mixture prior to a spectroscopic probe.…”
mentioning
confidence: 99%
“…These clusters exhibit a high capacity for adsorbing molecules of other gases. For example, it was experimentally found that water clusters with a size of up to nine atoms are capable of capturing and holding a benzene molecule whose molecular weight is half the weight of such cluster [3]. Previously, the method of molecular dynamics in the approximation of hard TIP4P model of water was used to demonstrate [4] that, as a result of the attachment of O 2 molecules to (H 2 O) n clusters, the absorption coefficient decreases, and reflection coefficient increases.…”
Section: Introductionmentioning
confidence: 99%